2001
DOI: 10.1063/1.1386783
|View full text |Cite
|
Sign up to set email alerts
|

Collisional quenching of high rotational levels in A 2Σ+ OH

Abstract: Collisional removal of the v′=0 level of the A 2Σ+ state of the OH radical has been studied as a function of rotational level N′ at room temperature. OH in high rotational levels of the X 2Πi state were created by 193 nm photolysis of HNO3 and excited to A 2Σ+ by a tunable dye laser. Time decays of fluorescence at varying pressures were measured. For O2 and H2, the quenching cross section σQ decreased with increasing N′ until N′∼10; for higher N′ it appears to remain approximately constant. Xe behaves the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 26 publications
5
41
0
Order By: Relevance
“…Early kinetics studies identified a trend of decreasing cross section with increasing temperature for many molecular quenchers, which was attributed to an attractive interaction between OH A 2 + and the molecular collision partner. [2][3][4][5][6][7] More recently, Han and co-workers obtained this same trend in their nonadia- batic quantum reactive scattering calculations for OH A 2 + + H 2 /D 2 . 23,24 They found reactive quenching to be the dominant process, yet the calculated integral cross section for reactive quenching decreased with increasing collision energy in the 0.06 to 0.40 eV range examined.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Early kinetics studies identified a trend of decreasing cross section with increasing temperature for many molecular quenchers, which was attributed to an attractive interaction between OH A 2 + and the molecular collision partner. [2][3][4][5][6][7] More recently, Han and co-workers obtained this same trend in their nonadia- batic quantum reactive scattering calculations for OH A 2 + + H 2 /D 2 . 23,24 They found reactive quenching to be the dominant process, yet the calculated integral cross section for reactive quenching decreased with increasing collision energy in the 0.06 to 0.40 eV range examined.…”
Section: Discussionsupporting
confidence: 54%
“…The rate of this collisional quenching process has been studied for a variety of molecular partners over a wide range of temperatures and initial OH A 2 + rotational states. [2][3][4][5][6][7] In general, the rates were found to decrease with increasing temperature and OH A 2 + rotational excitation, indicating that quenching is controlled by an attractive interaction with a significant OH orientation dependence. [4][5][6][7] Several empirical models have been proposed to explain the quenching phenomena, 2,[8][9][10][11] yet only recently has the mechanism for quenching of OH A 2 + by even simple molecular partners (H 2 , N 2 ) become evident from experiment and first-principles theory.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Quenching of OH A 2 ⌺ + by molecular collision partners has been the focus of a great deal of attention in literature, stemming largely from the practical importance of OH as a reactive species in atmospheric and combustion chemistry 14,15 and the application of LIF on the A 2 ⌺ + − X 2 ⌸ band system 16 to probe absolute concentrations and temperatures in these environments. The phenomenon manifests itself as decreased fluorescence lifetime as a function of collision partner pressure, and hence a decrease in the fluorescence quantum yield.…”
Section: Introductionmentioning
confidence: 99%
“…These reactions (and isotopic analogues) have generated substantial experimental interest in recent years. [8][9][10][11][12][13][14][15][16][17] Moreover, there has been significant theoretical interest in the electronic structure and conical intersections of this system, 10,18,19 and in the general question of adiabatic to diabatic transformations (ADTs) in molecules with conical intersections. [20][21][22][23][24] As a consequence, this system represents a benchmark test case for the development of theoretical reaction dynamics for polyatomic molecules in multiple electronic states.…”
Section: Introductionmentioning
confidence: 99%